Instilling the Environmental Care Characters to the Elementary Schools Located on the River Banks - Rabiatul Adawiah (Center for Journal Management and Publication, 2018)
School is one of the spearheads to achieve the function of shaping human character who care about the environment. Schools can implement strategies to instill students' awareness of the environment as early as possible. The learning process in schools is very possible to form and instill the environmental care characters. This study aims to find the students' attitudes and behaviors toward the environmental care, the school strategy in instilling the environmental care, and the constraints faced in embedding environmental care characters. The approach used is a qualitative approach. The data were collected through observation, interviews, and questionnaires. The data obtained were analyzed with the interactive model of analysis from Miles and Huberman. The results of the study indicated the students’ character and behavior of the environmental care were on the very good category (50%) and good (33%), the remaining categories were fair (9%), less good (5%) and poor (3%). The efforts made by schools to enable students to be aware of the environment are: to integrate it to the learning, to model, to habituate, and to insert messages to care to the environment every flag ceremony held on Mondays. The obstacles encountered in embedding the environmental care characteristics are customs in the family and less good model from the parents and people around about the environmental care.